Effects of neighborhood socioeconomic status on blood pressure in older adults - Katia Jakovljevic Pudla Wagner; Antonio Fernando Boing; SV Subramanian; Doroteia Aparecida Höfelmann; Eleonora D'Orsi
ABSTRACT OBJECTIVE To test if the neighborhood socioeconomic status is associated with systolic blood pressure and hypertension in older adults. METHODS A cross-sectional population-based study with a sample of 1,705 older adults from Florianópolis, SC, Southern Brazil. The contextual variable used was the average years of schooling of the head of the household in census tracts. Participants were considered hypertensive when the systolic blood pressure was ≥ 140 mmHg, diastolic ≥ 90 mmHg, or both. Additionally, the use of antihypertensive medication was also considered. Data were analyzed by using multilevel models of logistic and linear regression. RESULTS The average age of the sample was 70.7 years and the average of systolic and diastolic blood pressure was 133.5 mmHg (SD = 20.5 mmHg) and 81.9 mmHg (SD = 12.5 mmHg), respectively. The systolic blood pressure was 4.46 mmHg (95%CI 1.00-7.92) higher and the chance of hypertension was 1.80 (95%CI 1.26-2.57) among those who lived in census tracts with lower level of schooling. When the use of antihypertensive medication was combined with blood pressure levels, none association was found between the outcome and the level of schooling of the census tract. CONCLUSIONS Analytical models more robust (such as multilevel analysis) in Brazil are still little used, with a small number of articles published. Neighborhood socioeconomic status is associated with systolic blood pressure and the chance of hypertension, regardless of individual characteristics.